Comfort in automated driving: An analysis of preferences for different automated driving styles and their dependence on personality traits. (May 2018) - Bellem, Hanna; Thiel, Barbara; Schrauf, Michael; Krems, Josef F.
Highlights: Comfort of automated lane changes, accelerations and decelerations was analyzed. For lane changes, low jerks and early motion feedback are advisable. In direct comparison, deceleration mirroring manual behavior is favored least. Symmetrical accelerations are experienced as more comfortable. The analyzed personality traits do not seem to have a big influence on preferences. Abstract: As technical realization of highly and fully automated vehicles draws closer, attention is being shifted from sheer feasibility to the question of how an acceptable driving style and thus comfort can be implemented. It is increasingly important to determine, how highly automated vehicles should drive to ensure driving comfort for the now passive drivers. Thus far, only little research has been conducted to examine this issue. In order to lay a basis on how automated vehicles should drive to ensure passenger comfort, different variations of three central maneuvers were rated and analyzed. A simulator study (N = 72) was conducted in order to identify comfortable driving strategies. Three variations of lane changes, accelerations and decelerations were configured by manipulating acceleration and jerk, and thus the course of each maneuver. Furthermore, the influence of personality traits and self-reported driving style on preferences of differently executed automated maneuvers was analyzed. Results suggest keeping acceleration and jerk as small as possible for acceleration maneuvers. For lane changes, both small accelerations as well as an early motion feedback are advisable. Interestingly, decelerating as a manual driver would is rejected compared to two artificial alternatives. Moreover, no influence of personality traits on maneuver preference was found. Only self-reported driving style had a marginal effect on participants' preferences. In conclusion, a recommendation for an automated driving style can be given, which was perceived as comfortable by participants regardless of their personality.